The physician shortage in Israel and a policy proposal for improvement - Yulia Treister-Goltzman; Roni Peleg (BMC, 2023)
Abstract Background There is a decrease in the supply of physicians in Israel resulting from the declining flow of immigrant physicians from the former Soviet Union, a large proportion of whom have reached retirement age in recent years. This problem could become worse because the number of medical students in Israel cannot increase quickly, especially because the number of clinical training sites is inadequate. The quick population growth and anticipated ageing will exacerbate the shortage. The aim of our study was to accurately assess the current situation and factors that affect it, and to propose systematic steps to improve the physician shortage. Main body The number of physicians per capita is lower in Israel than in the OECD at 3.1 vs. 3.5 per 1000 population, respectively. About 10% of licensed physicians live outside of Israel. There is a sharp increase in the number of Israelis returning from medical school abroad, but some of those schools are of low academic standard. The main step is a gradual increase in the number of medical students in Israel with a transition of clinical practice to the community, and hospital clinical hours in the evening and in the summer. Students with high psychometric scores who were not admitted to an Israeli medical school would get support to study in quality medical schools abroad. Additional steps include encouraging physicians from abroad to come to Israel, especially in specializations in distress, recruitment of retired physicians, transferring functions to other medical professions, economic incentives for departments and teachers, and incentives to prevent physicians from quitting or migrating to other countries. It is also important to close the gap between the number of physicians working in central Israel and the periphery through grants, employment opportunities for physicians' spouses, and preferential selection of students from the periphery for medical school. Conclusions Manpower planning requires a broad, dynamic perspective and collaboration among governmental and non-governmental organizations.